Acquired Reactive Perforating Collagenosis Complicated by Diabetes Mellitus and Hypertension: A Case Report - Zhang, Meng; Chu, Ruiqi; Shen, Junping; Liu, Chunmei; Wang, Yanan; Zhang, Shun; Ren, Xiangxiang (Case reports in dermatology, 2025)
Introduction: Acquired reactive perforating collagenosis (ARPC) is a rare cutaneous disorder frequently associated with systemic diseases such as diabetes mellitus and chronic kidney disease. Its diagnosis remains challenging due to clinical overlap with other perforating dermatoses, necessitating advanced diagnostic tools for confirmation. Case Presentation: A 55-year-old male with a 15-year history of diabetes mellitus and hypertension developed progressively pruritic papules and nodules on both lower limbs over 2 months. Initial misdiagnosis as a fungal infection led to unsuccessful antifungal therapy. Dermatoscopy revealed keratotic plugs with peripheral erythema, while histopathology demonstrated transepidermal elimination of degenerated collagen, confirming ARPC. Topical retinoic acid cream achieved marked symptomatic relief. Conclusion: This case highlights ARPC’s strong association with metabolic comorbidities and underscores the necessity of dermatoscopic and histopathological evaluation to avoid diagnostic pitfalls. The therapeutic success of topical retinoids in resource-constrained settings reinforces their role as a pragmatic first-line intervention. Clinicians should consider ARPC in patients with chronic pruritic eruptions and systemic metabolic disorders, advocating for multidisciplinary collaboration to address underlying comorbidities.